Polypropylene composite material, and preparation method and application thereof

CN119842147BActive Publication Date: 2026-10-27KINGFA SCI & TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411967267.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2026-10-27
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

[0005]现有技术中对尼龙、聚碳酸酯和PBT等工程塑料为主的研究,对于聚丙烯紫外激光打标参考意义不大

Benefits of technology

本发明提供的一种浅色聚丙烯复合材料可用于紫外激光打标,能够广泛应用于电子元器件、白色家电外壳和汽车内外饰等行业和领域,经过紫外激光打标后,该材料可以呈现清晰的激光标识效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of high polymer materials, and particularly relates to a polypropylene composite material, a preparation method and application thereof. Specifically, the polypropylene composite material comprises the following components in parts by weight: 95-105 parts of polypropylene resin; 5-20 parts of flame retardant; 1-5 parts of antioxidant; 1-3 parts of light stabilizer; and 0.5-5 parts of composite pigment, wherein the composite pigment is obtained by compounding titanium white and carbon black, and the weight ratio of the titanium white to the carbon black is (2500-20000):1. The polypropylene composite material provided by the application can be used for ultraviolet laser marking, and has a clear laser marking effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a polypropylene composite material, its preparation method, and its application. Background Technology

[0002] As a thermoplastic synthetic resin, polypropylene (PP) has the advantages of low density, electrical insulation, chemical resistance, excellent weather resistance, easy processing, and easy recycling, and is widely used in industries such as automobiles, home appliances, power tools, and packaging.

[0003] In actual parts manufacturing, manufacturers need to mark products with company names, product specifications, serial numbers, anti-counterfeiting information, etc., to improve product identification and achieve production traceability. Traditional marking technologies for polypropylene products include chemical screen printing, painting, and film application. Laser marking, on the other hand, utilizes the high energy density of a laser beam to cause chemical or physical changes in the surface material of the workpiece, leaving a permanent mark. It offers advantages such as being pollution-free, high-speed, high-quality, highly flexible, and non-contact with the workpiece. Laser marking is gradually replacing traditional marking technologies, its applications are becoming increasingly widespread, and it has become the mainstream technology in the industry. Infrared laser marking, due to its inherent characteristics such as wavelength, pulse width, and current power, suffers from severe processing heat effects, making it unable to meet the needs of more refined processing and manufacturing. Ultraviolet laser marking technology, due to its high single-photon energy, can directly break the intermolecular forces, causing non-thermal damage to the material and leaving a permanent mark on the material surface. It has developed rapidly and become a reliable choice for material marking technology.

[0004] There is relatively more research on laser marking, with infrared laser marking technology being more extensively studied than ultraviolet laser marking technology. This is because infrared laser marking technology was developed earliest and is the most maturely applied in the manufacturing industry, exhibiting a certain technological inertia. Ultraviolet laser marking technology, on the other hand, emerged after the demand for fine marking developed, and its application in the modified plastics industry is currently relatively limited, making it a relatively new technological field. Research on modified plastics primarily focuses on engineering plastics such as nylon, polycarbonate, and PBT, with less research on polypropylene modified materials.

[0005] Existing research, primarily focusing on engineering plastics such as nylon, polycarbonate, and PBT, offers limited reference value for UV laser marking of polypropylene. Therefore, providing a light-colored polypropylene composite material suitable for UV laser marking is of practical significance. Summary of the Invention

[0006] The purpose of this invention is to provide a light-colored flame-retardant polypropylene composite material that can be used for ultraviolet laser marking.

[0007] Another object of the present invention is to provide a preparation process for the above-mentioned polypropylene composite material.

[0008] Another object of the present invention is to provide applications of the above-mentioned polypropylene composite material.

[0009] This invention is achieved through the following technical solution: A polypropylene composite material, characterized in that it comprises the following components in parts by weight: 95-105 parts of polypropylene resin; 5-20 parts flame retardant; Antioxidant 1-5 parts; 1-3 parts light stabilizer; 0.5-5 parts of composite pigment; The composite pigment is obtained by compounding titanium dioxide and carbon black; the weight ratio of titanium dioxide to carbon black is (2500-20000):1.

[0010] In composite pigments, carbon black acts as a light absorber to absorb photons.

[0011] In this invention, the titanium dioxide is rutile pigment titanium dioxide, preferably with a particle size of 0.20-0.25 μm; the carbon black is selected from pigment carbon black obtained by acetylene thermal decomposition, and the preferred particle size of the carbon black is 20-35 nm.

[0012] Preferably, the melt index of the polypropylene resin is 1-30 g / 10min, the testing conditions are a temperature of 230℃ and a load of 2.16 kg, and the testing standard is ISO 1133-1-2011.

[0013] Preferably, the composite pigment accounts for 1-4 parts by weight in the polypropylene composite material.

[0014] Preferably, the polypropylene resin is selected from at least one of homopolymer polypropylene resin or copolymer polypropylene resin.

[0015] More preferably, the polypropylene resin is selected from homopolymer polypropylene.

[0016] The polypropylene composite material provided by this invention can be used for ultraviolet laser marking. The light source wavelength of ultraviolet laser marking equipment is usually 355nm. At this wavelength, homopolymer polypropylene has a better marking effect.

[0017] Preferably, the flame retardant is selected from flame retardants containing metal elements, which can enhance the absorption of ultraviolet photons and energy conduction of the material, making the marking effect stronger; the metal element is antimony or titanium.

[0018] Further preferred, the flame retardant is a flame retardant containing antimony or titanium.

[0019] The reason why flame retardants containing the above-mentioned metal elements have better effects is that the ionization energy of the outer electrons of antimony and titanium metal oxides or complexes is close to that of ultraviolet photons. Therefore, they can absorb ultraviolet photon energy and undergo transitions, converting light energy into internal energy, which greatly promotes the marking effect.

[0020] Preferably, the antioxidant is selected from phosphite antioxidants and hindered phenolic antioxidants; the weight ratio of the phosphite antioxidant to the hindered phenolic antioxidant is (1-3):1.

[0021] Further preferably, the weight ratio of the phosphite antioxidant and the hindered phenolic antioxidant is (1.5-2.5):1.

[0022] Specifically, the phosphite antioxidant is selected from tris(2,4-di-tert-butylphenyl) phosphite; the hindered phenolic antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0023] Preferably, the light stabilizer is selected from at least one of hindered amine light stabilizers, benzotriazole light stabilizers, benzophenone light stabilizers, or hindered benzoate light stabilizers.

[0024] Specifically, the hindered amine light stabilizer is selected from 2,2,6,6-tetramethyl-4-piperidine stearate.

[0025] Preferably, the titanium dioxide is selected from rutile titanium dioxide.

[0026] Preferably, the weight ratio of titanium dioxide to carbon black is (4000-6000):1.

[0027] More preferably, the weight ratio of the titanium dioxide to carbon black is 5000:1.

[0028] This invention provides a method for preparing the above-mentioned polypropylene composite material, comprising the following steps: (1) Weigh each component according to the ratio and put them into the premixer in sequence. Mix for 6-8 minutes until a uniform mixture is achieved. (2) The mixed material is fed into a twin-screw extruder with a screw length-to-diameter ratio of 30:1-40:1. The extruder temperature is set at 100-130℃ in zone T1, 190-205℃ in zone T2-T5, and 205-210℃ in zone T6-T12. The speed is 300-450 r / min. After mixing, melting, and homogenizing, the material is extruded and granulated to obtain a light-colored flame-retardant polypropylene composite material that can be used for UV marking.

[0029] The present invention also provides the application of the above-mentioned polypropylene composite material for ultraviolet laser marking.

[0030] The polypropylene composite material provided by this invention can also be used to prepare products that require ultraviolet laser marking.

[0031] Compared with the prior art, the present invention has the following advantages: The present invention provides a light-colored polypropylene composite material that can be used for ultraviolet laser marking and can be widely applied in industries and fields such as electronic components, white goods housings and automotive interior and exterior trim. After ultraviolet laser marking, the material can present a clear laser marking effect. Detailed Implementation

[0032] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0033] Sources of raw materials used in this invention: PP Resin 1: PP HP500N; homopolymer polypropylene, with a melt flow rate of 12g / 10min at a temperature of 230℃ and a load of 2.16kg, CNOOC Shell Petrochemicals Co., Ltd.

[0034] PP Resin 2: PP T30S (Daqing Petrochemical), homopolymer polypropylene, with a melt flow rate of 3.0 g / 10 min at a temperature of 230℃ and a load of 2.16 kg, Daqing Petrochemical.

[0035] PP Resin 3: PP EP548R, copolymer polypropylene, melt flow rate of 28g / 10min at 230℃ and 2.16kg load, Suzhou Guihai Plastics Co., Ltd. and Guangzhou Tuma Chemical Co., Ltd.

[0036] PP Resin 4: PP EPS30R, copolymer polypropylene, melt flow rate of 1.5g / 10min at 230℃ and 2.16kg load, Shandong Qilu Petrochemical Plant Co., Ltd.

[0037] Flame retardant 1; S-05N, composed of antimony trioxide, is a type of antimony flame retardant, manufactured by Changde Chenzhou Antimony Products Co., Ltd.

[0038] Flame retardant 2: XZ-6800 granules, composed of octabromoether, a type of bromine-based flame retardant, manufactured by Shandong Brothers Technology Co., Ltd.

[0039] Flame retardant 3: MCA, composed of melamine cyanurate, Shandong Haiwang Chemical Co., Ltd.

[0040] Flame retardant 4:2500-G, composed of modified ultrafine magnesium hydroxide, is a type of hydroxide flame retardant, manufactured by Yingkou Global Powder Engineering Co., Ltd.

[0041] Antioxidant 1: Phosphite antioxidant, YFK-168, Yingkou Fengguang Chemical Co., Ltd.

[0042] Antioxidant 2: Hindered phenolic antioxidant, YFK-1010, Yingkou Fengguang Chemical Co., Ltd.

[0043] Light stabilizer: Hindered amine light stabilizer, UV-3808PP5, Cytec Surface Technology (Shanghai) Co., Ltd.

[0044] Composite Pigment 1: It is obtained by compounding titanium dioxide and carbon black in a weight ratio of 5000:1. The titanium dioxide is rutile titanium dioxide, TR-33, with a particle size of 0.22um, from Shanghai Yantai Industrial Co., Ltd.; the carbon black is magicab 1013F, with a primary particle size of 24±2nm, from Shenzhen Dingtai Chemical Co., Ltd.

[0045] Composite Pigment 2: It is obtained by compounding titanium dioxide and carbon black in a weight ratio of 10000:1. The titanium dioxide is rutile titanium dioxide, TR-33, with a particle size of 0.22um, from Shanghai Yantai Industrial Co., Ltd.; the carbon black is magicab 1013F, with a primary particle size of 24±2nm, from Shenzhen Dingtai Chemical Co., Ltd.

[0046] Composite pigment 3: It is obtained by compounding titanium dioxide and carbon black in a weight ratio of 2000:1. The titanium dioxide is rutile titanium dioxide, TR-33, with a particle size of 0.22um, from Shanghai Yantai Industrial Co., Ltd.; the carbon black is magicab 1013F, with a primary particle size of 24±2nm, from Shenzhen Dingtai Chemical Co., Ltd.

[0047] Test method: Ultraviolet laser marking performance (ΔE): S1: Use a UV-3X ultraviolet laser marking machine (wavelength 355nm) to scan and mark a circular mark with a diameter of 25mm on the surface of a standard color swatch according to fixed process parameters. The specific operation steps are as follows: First, import the vector image of the pattern to be marked into EzCad 2.0 software; second, set appropriate power, scanning speed and other relevant marking process parameters; finally, preview the marking position and marking pattern, and complete the marking after confirming that there are no errors.

[0048] S2: Use a Datacolor Sepctro 1050 colorimeter to measure the color data L0, a0, b0 of the color sample before UV laser marking and the color data L1, a1, b1 of the circular area after laser marking. The color difference ΔE before and after marking is used to characterize the effect of UV laser marking. The specific algorithm is as follows:

[0049] Where △L = L1 - L0, △a = a1 - a0, △b = b1 - b0.

[0050] The embodiments and comparative examples in this invention were prepared through the following steps: The mixed material is fed into a twin-screw extruder, and after mixing, melting, homogenization, and extrusion granulation, a light-colored flame-retardant polypropylene composite material that can be used for UV marking is obtained.

[0051] The twin-screw extruder has a length-to-diameter ratio of 30:1, and the extrusion temperature is set to 100~130℃ in zone T1, 190~205℃ in zones T2~T5, and 205~210℃ in zones T6~T12. The rotation speed is 350r / min.

[0052] Table 1. Components and test results of polypropylene composite materials in Examples 1-9 PP resin 1 95 105 100 100 100 100 PP resin 2 100 PP resin 3 100 PP resin 4 100 Flame retardant 1 20 5 5 10 15 20 15 15 15 Antioxidant 1 2.5 0.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Antioxidant 2 2.5 0.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Light stabilizers 3 1 3 3 3 3 3 3 3 Composite color powder 1 5 0.5 4 4 4 4 4 4 4 Ultraviolet laser marking performance (ΔE) 36.31 35.88 38.19 42.48 48.36 46.79 47.81 45.33 42.98 As can be seen from Examples 3-6, increasing the amount of flame retardant initially improves the laser marking performance, but then decreases it.

[0053] As can be seen from Examples 5 and 7-9, the effect of copolymer PP resin is worse than that of homopolymer PP resin.

[0054] Table 2. Components and Test Results of Polypropylene Composites in Examples 10-21 PP resin 1 100 100 100 100 100 100 100 100 100 100 100 100 Flame retardant 1 15 15 15 15 15 15 15 15 15 Flame retardant 2 15 Flame retardant 3 15 Flame retardant 4 15 Antioxidant 1 0.5 2.5 1.5 1.5 1.5 2 2.5 1.5 1.5 1.5 1.5 1.5 Antioxidant 2 0.5 2.5 1.5 1.5 1.5 1 0.5 1.5 1.5 1.5 1.5 1.5 Light stabilizers 3 3 3 3 3 3 3 3 3 3 3 3 Composite color powder 1 4 4 0.5 2 5 4 4 4 4 4 Composite color powder 2 4 Composite color powder 3 4 Ultraviolet laser marking performance (ΔE) 39.26 47.22 36.73 37.82 47.88 49.55 42.57 39.75 41.22 43.35 43.99 37.85 As can be seen from Examples 10-11, adjusting the amount of antioxidant added can affect the laser marking performance.

[0055] As can be seen from Examples 5 and 12-14, the amount of composite pigment added is not necessarily better the higher it is. It is speculated that this is because carbon black is a black pigment, and increasing the amount of carbon black will reduce the whiteness of the material's base color, resulting in a smaller color difference before and after UV laser marking, which manifests as a decrease in UV laser marking performance.

[0056] As can be seen from Examples 5 and 15-16, the preferred weight ratio of phosphite antioxidants to hindered phenolic antioxidants is (1-3):1.

[0057] As can be seen from Examples 5 and 20-21, the ratio of titanium dioxide to carbon black in the composite pigment affects the UV laser marking performance. The preferred weight ratio of titanium dioxide to carbon black is (4000-6000):1.

[0058] As can be seen from Examples 1-21, the performance test result △E > 35 of the polypropylene composite material provided by the present invention after ultraviolet laser marking, indicating that the polypropylene composite material provided by the present invention has good ultraviolet laser marking performance.

[0059] Table 3. Comparative Examples 1-4: Components of Polypropylene Composites and Their Test Results PP resin 1 100 100 100 100 Flame retardant 1 15 15 / 35 Antioxidant 1 1.5 1.5 1.5 1.5 Antioxidant 2 1.5 1.5 1.5 1.5 Light stabilizers 3 3 3 3 Composite color powder 1 0.2 15 4 4 Ultraviolet laser marking performance (ΔE) 28.91 29.67 23.36 27.88 As can be seen from Comparative Examples 1-2, when the amount of composite pigment added does not reach the minimum required level or exceeds the maximum required level, the UV laser marking performance ΔE < 30.

[0060] As can be seen from Comparative Examples 3-4, the performance of UV laser marking will also decrease significantly when no flame retardant is added or when an excessive amount of flame retardant is added.

Claims

1. A polypropylene composite material for laser marking, characterized in that, It consists of the following components by weight: 95-105 parts of polypropylene resin; 5-20 parts flame retardant; Antioxidant 1-5 parts; 1-3 parts light stabilizer; 0.5-5 parts of composite pigment; The composite pigment is obtained by compounding titanium dioxide and carbon black; the weight ratio of titanium dioxide to carbon black is (4000-6000):

1. The flame retardant is selected from at least one of antimony-based flame retardants, bromine-based flame retardants, melamine cyanurate, and hydroxide flame retardants.

2. The polypropylene composite material for laser marking according to claim 1, characterized in that, The melt flow index of the polypropylene resin is 1-30 g / 10min; the testing standard is ISO 1133-1-2011, and the testing conditions are a temperature of 230℃ and a load of 2.16 kg.

3. The polypropylene composite material for laser marking according to claim 1, characterized in that, The polypropylene resin is selected from at least one of homopolymer polypropylene resin or copolymer polypropylene resin.

4. The polypropylene composite material for laser marking according to claim 3, characterized in that, The polypropylene resin is homopolymer polypropylene.

5. The polypropylene composite material for laser marking according to claim 1, characterized in that, The flame retardant is selected from antimony-based flame retardants.

6. The polypropylene composite material for laser marking according to claim 1, characterized in that, The antioxidant is selected from phosphite antioxidants and hindered phenolic antioxidants; the weight ratio of the phosphite antioxidant to the hindered phenolic antioxidant is (1-3):

1.

7. The polypropylene composite material for laser marking according to claim 6, characterized in that, The weight ratio of the phosphite antioxidant to the hindered phenolic antioxidant is (1.5-2.5):

1.

8. The polypropylene composite material for laser marking according to claim 1, characterized in that, The light stabilizer is selected from at least one of hindered amine light stabilizers, benzotriazole light stabilizers, benzophenone light stabilizers, or hindered benzoate light stabilizers.

9. The polypropylene composite material for laser marking according to claim 1, characterized in that, The titanium dioxide is selected from rutile titanium dioxide.

10. The method for preparing the polypropylene composite material for laser marking according to any one of claims 1-9, characterized in that, Includes the following steps: (1) Weigh each component according to the ratio, put them into the premixer in sequence, and mix them evenly; (2) The mixed material is fed into a twin-screw extruder, and after mixing, melting, homogenization and extrusion granulation, the polypropylene composite material for laser marking is obtained.

11. The application of the polypropylene composite material for laser marking according to any one of claims 1-9, characterized in that, Used for ultraviolet laser marking.

Citation Information

Patent Citations

  • White polypropylene material capable of realizing laser marking, preparation method and application thereof

    CN113845731A